Formulettes éducatives de première enfance chez les Franco-Terreneuviens: une tradition mixte - Thomas, Gerald (Ethnologies, 1981)
AbstactBy means of the educational formulae of infancy, the author illustrates some stages in the assimilation of francophones by the anglophones on the Port-au-Port peninsula. After having recounted the salient events of the French presence on the west coast of Newfoundland from Cartier's first voyage in 1534 up to the construction of an American airforce base in 1941 (which rapidly initiated the assimilation, unknown until that time), the author presents an intermingling of French and English formulae to illustrate his subject. He concludes that there is a need for collaboration among folklorists, psychologists, and linguists on this subject, which has not yet interested folkorists greatly.